Teknik dan Strategi Menghitung HPP dalam Rangka Eskalasi Penjualan pada UMKM Gading Bersinar, Depok - Widiyati, Dian; Hasanah, Neneng; Napisah (Rengganis Jurnal Pengabdian Masyarakat, 2023)
Micro, Small and Medium Enterprises (MSMEs) have a very important role in the Indonesian economy. The main problem that MSMEs often face is how to carry out appropriate financial strategies in business management. One of them is the calculation of the Cost of Goods Sold (HPP) which has quite a significant influence in terms of sales escalation. Gading Bersinar UMKM is an association of small and medium traders in the Curug area, Depok. These MSMEs come from various educational backgrounds, meaning that most business actors do not have sufficient knowledge and knowledge regarding good HPP recording. The products they sell are varied, including selling clothes, food, handicrafts and home-cooked food products. In this regard, the PKM activities carried out discuss the Cost of Goods Sold, starting from the definition, components, calculations and implementation of the Cost of Goods Sold in the MSME. From the results of community service activities regarding Techniques and Strategies for Calculating Cost of Goods Sold in the Context of Sales Escalation, it can be concluded that to increase MSME sales, the steps that need to be taken are to improve techniques and strategies in calculating COGS according to the situation, conditions and problems that arise. With careful HPP planning, this will help increase MSME sales.